The changing role of the subject specialist - Cotta-Schønberg, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
As we all know, libraries are these years rapidly undergoing change on unparalleled scale. Evidently, this applies to librarians, too, and not the least to that important category of library staff, the subject specialist. As recruiting and education of library workers differ from country to country it is difficult to give a detailed, generally valid description of the subject librarian in libraries, but I believe that you can describe an ideal model of subject librarianship as follows: Within each of the major subject disciplines covered by the library, the library should have a subject specialist preferably with a master degree or at least a bachelor degree in the particular subject discipline. The role of the subject specialist is to perform four basic functions where extensive subject knowledge is considered to be necessary: selecting and classifying books, assisting users with advanced subject inquiries, giving subject-specific courses in information retrieval, and maintaining liaison with relevant academic departments and centres. Personally, I know this system very well since I got employment in the Royal Library in Copenhagen as a subject specialist in psychology in the very month I finished my degree in psychology from the University of Copenhagen, back in 1973. The subject librarian system at the Royal Library in Copenhagen was patterned on the ideal model, as I just described it, and it was closely paralleled in the other academic libraries in Denmark, also the new university libraries which were founded in the seventies.